2007
DOI: 10.1097/jcp.0b013e31815abefb
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Modafinil and a Selective Serotonin Reuptake Inhibitor From the Initiation of Treatment of Major Depressive Disorder With Fatigue and Sleepiness

Abstract: Power to detect differences between modafinil and placebo was limited because of the premature discontinuation of the trial. Although modafinil did not show evidence of benefit over placebo on the Epworth Sleepiness Scale, secondary measures suggested modafinil may have provided benefit for symptoms of excessive sleepiness in patients with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 25 publications
1
30
0
2
Order By: Relevance
“…[8] Most guidelines have suggested that nonresponders or partial responders should be considered for switch, combination or augmentation treatment. [9][10][11][12] Traditional augmentation agents such as lithium, triiodothyronine (T3), buspirone, [13] azapirone, [14] dopamine agonists (including pramipexole and ropinirole), [15,16] modafinil [17][18][19][20][21][22][23] and stimulants (including methylphenidate) [12,24] have been commonly used for this patient population, but with limited supporting data. Recently, augmentation of antidepressant therapy with atypical antipsychotics has become a more commonly accepted treatment practice.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Most guidelines have suggested that nonresponders or partial responders should be considered for switch, combination or augmentation treatment. [9][10][11][12] Traditional augmentation agents such as lithium, triiodothyronine (T3), buspirone, [13] azapirone, [14] dopamine agonists (including pramipexole and ropinirole), [15,16] modafinil [17][18][19][20][21][22][23] and stimulants (including methylphenidate) [12,24] have been commonly used for this patient population, but with limited supporting data. Recently, augmentation of antidepressant therapy with atypical antipsychotics has become a more commonly accepted treatment practice.…”
Section: Introductionmentioning
confidence: 99%
“…Modafinil, a newer stimulant which has been proposed to have a mechanism of action independent of its effects on dopamine, has been investigated as an augmenting agent in two large, placebo-controlled trials. Initial improvement in depressive symptoms seen with modafinil was not sustained, although apathy and fatigue remained significantly improved from baseline 92 93. A subsequent retrospective pooled analysis suggested that modafinil augmentation may improve depression in TRD patients with significant sleepiness and fatigue 92…”
Section: Pharmacotherapy For Trdmentioning
confidence: 97%
“…Two large randomized controlled trials of lisdexamfetamine in the treatment of MDD in SSRI non-remitters revealed no efficacy of the psychostimulant (Shrie, 2014). A double blind, placebo-controlled study assessed adjunctive modafinil or placebo (to an SSRI) and found that modafinil did not have any benefit (Dunlop et al, 2007). A Cochrane review published in 2008 included 13 trials for metaanalysis.…”
Section: Stimulant Augmentationmentioning
confidence: 98%